Identification and treatment of Enterococcus avium-induced diabetic foot ulcer: a case report and microbiome analysis - Jin, Yuanling; Zhu, Tao; Cai, Xiao; Fu, Zheng; Pan, QiangLong; Tu, HaiXia; Wang, ShouXing; Li, Yan (Frontiers in Medicine, 2024)
AbstractDiabetic foot ulcer (DFU) is a severe complication of diabetes. Due to conservative or delayed treatment, the majority of DFU patients frequently miss the optimal treatment window, thereby leading to amputation. Despite being a rare pathogen with low virulence, Enterococcus avium (E. avium) exhibits some antibiotic resistance and can be fatal for immunocompromised patients. This report describes a DFU case, caused by E. avium infection due to exposure to poultry. Wound microbiota was dynamically monitored using bacterial culture followed by 16S rRNA gene sequencing throughout the illness. Combination of antibiotics was administered to control the secondary infection.Case reportA 56-year-old man presented with a two-week history of redness, swelling, heat, pain, and pus discharge from a ruptured wound on his left heel. The patient was diagnosed with osteomyelitis and a Wagner grade 3 diabetic foot ulcer infection, complicated by the soft tissue infection in the left heel. Strain identification and antibiotic susceptibility tests were immediately performed after admission. The patient underwent three debridement procedures at the DFU site. However, we observed recurrent bacterial infections, based on the clinical progression. Second-generation sequencing detected various pathogens. After targeted treatment with Vacuum sealing drainage (VSD) combined with antibiotic bone cement, the patient’s condition stabilised. A skin graft was subsequently performed. Antibiotics were used to control the infection and blood glucose level was controlled throughout the treatment.ConclusionThus, this report provides a comprehensive description of a DFU case, caused by E. avium. Antibiotics and surgical measures should be adjusted according to the pathogens responsible for wound infections in DFU patients. It is important to reduce the mortality and prevent irreversible amputations.